Genetic barcoding of flatfishes reveals diverse species distribution patterns along the Tanzanian coast - Lisa G. Peter; Jackson L. Saiperaki; Jibril Olunga; Charles M. Lyimo; Levy M. Otwoma; Cyrus Rumisha; Marc Kochzius (Western Indian Ocean Journal of Marine Science, 2026)
Flatfishes are important components of benthic communities and support small-scale fisheries that sustain livelihoods in the southwestern Indian Ocean. However, limited data on their diversity and distribution hinder effective management and conservation, especially under growing threats from destructive fishing and climate change. To address this, 134 flatfish specimens from the Tanzanian coast were analyzed. Specimens were initially identified through morphological examination and their species identities were confirmed using DNA barcoding. Partial fragments of the cytochrome c oxidase subunit I gene were sequenced and the resulting sequences matched against the Barcode of Life Data System and GenBank databases. Nine flatfish species across five families were recorded: Bothus pantherinus, Cynoglossus acaudatus, Cynoglossus attenuatus, Cynoglossus durbanensis, Engyprosopon grandisquama, Paraplagusia bilineata, Pardachirus marmoratus, Psettodes erumei, and Pseudorhombus arsius. Species composition and distribution varied by location, with P. marmoratus being the dominant species and P. erumei showing the widest distribution. Engyprosopon grandisquama and P. bilineata were rare and restricted to specific habitats, suggesting their current IUCN Least Concern status should be reassessed. One Bothus sp could not be identified using existing reference databases. These findings highlight the need to expand genetic databases, strengthen monitoring, and protect key habitats to support flatfish conservation in the region.

Local knowledge corroborates threats of local extinctions in Kenya’s exploited reef fishes - Levy Michael Otwoma; Julia Obuya; Christopher Aura Mulanda; Victor Mwakha Alati; Iddy Munuphe; Jibril Olunga; Mathews Wafula; Jelvas Mwaura; Christian Chimimba (Marine Policy, 2025)

Seasonality of Fish Juvenile Community Structure and Diversity in a Tropical Seagrass Meadow of Watamu, Kenya - Alphine Mboga; James Mwaluma; Rose Kigathi; Bernards Okeyo; Noah Ngisiange; Jibril Olunga; Monika Winder; Margareth Kyewalyanga (Western Indian Ocean Journal of Marine Science, 2023)
Seagrass are important marine habitats that function as nursery grounds for juvenile fish. Human activities and other natural factors have contributed to their decline, and this has compromised their role as nurseries, specifically in non-continuous patchy seagrass beds. In this study, juvenile fish abundance from tropical seagrass beds of Watamu were examined, while testing the hypothesis that seagrass cover and seasonality influenced juvenile fish abundanceand diversity. Two sampling stations were identified, Watamu Blue Lagoon (WBL) and Watamu Beach (WB), based on seagrass cover, and were sampled for a period of 10 months that included two south-east monsoon (SEM) and two north-east monsoon (NEM) seasons. Monthly samples were collected by seining within the shallow seagrass habitats of WBL and WB. A total of 31 juvenile fish families were obtained, the dominant taxa being Lutjanidae and Siganidae. Seasonal and interannual variability in juvenile abundance was observed over the two years (p